Prognostic significance of the infiltration of CD163+ macrophages combined with CD66b+ neutrophils in gastric cancer - Xiaopei Huang; Yamin Pan; Jun Ma; Zhengchun Kang; Xiaowen Xu; Yan Zhu; Jikuai Chen; Wei Zhang; Wenjun Chang; Jiangbo Zhu (Cancer Medicine, 2018)
Abstract The polarization of tumor‐associated macrophages (TAMs) and tumor‐associated neutrophils (TANs), especially from the antitumoral phenotype to the protumoral phenotype under certain conditions, has an important influence on the progression of tumors. However, the interactions and combined prognosis of these cells are poorly known. Here, we detected the infiltration of CD68+ TAMs, CD163+ TAMs, and CD66b+ TANs in the specimens from 662 patients with GC by immunohistochemistry. The results showed that the infiltration of each of CD163+, CD68+, and CD66b+ cells in GC tissue was significantly increased and independently associated with GC prognosis. Strong collinearity (r = 0.690, P < 0.001) was found between the infiltration of CD163+ and CD68+ cells in GC, and multivariate Cox analysis confirmed the infiltration of CD163+ cells was a better predictor for prognosis than that of CD68+ cells. The combination of the infiltration of CD163+ and CD66b+ cells provided more accurate survival prediction than any individual marker. Patient subgroups with CD66blowCD163low (hazard ratio (HR) = 2.161; 95% confidence interval (CI)  = 1.266–3.688; P < 0.001), CD66bhighCD163high (HR = 3.575; 95% CI = 2.155–5.933; P < 0.001), and CD66blowCD163high (HR = 7.514; 95% CI = 4.583–12.312; P < 0.001) were gradually associated with shorter DFS when compared with the subgroup with CD66bhighCD163low. The similar result was also for DSS among the subgroups. Moreover, the two‐marker model could more effectively discriminate the prognosis among the patients with chemotherapy than that among those without chemotherapy. We concluded that CD163+ TAMs were a more valuable prognostic marker than CD68+ TAMs, and CD163+ TAMs combined with CD66b+ TANs could more precisely predict the prognosis of patients with GC.